2011
DOI: 10.1590/s0004-282x2011000700008
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial sonography as a diagnostic tool for Parkinson's disease: a pilot study in the city of Rio de Janeiro, Brazil

Abstract: In Brazil there is no systematic study on Transcranial Sonography (TCS), a neuroimaging method that depicts echogenic deep brain structures using ultrasound. Objective: To establish the percentage of subjects with permissive temporal windows and to address the ability of TCS of the substantia nigra (SN) to distinguish parkinsonian patients in a Brazilian sample. Method: We performed TCS using the Acuson X300 (Siemens, Germany) in 37 individuals: 23 with Parkinson's disease (PD) and 14 healthy controls. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…This procedure has been considered sensitive and reliable in detecting abnormalities of the basal ganglia of the brain, such as degeneration of the SN in idiopathic PD, lesion of the lentiform nucleus in idiopathic dystonia, and degeneration of the SN and the caudate nucleus in Huntington's disease, among others. The method is also useful in the differential diagnosis of movement disorders and to clarify some of their pathophysiological mechanisms (12)(13)(14)(15)(16) .…”
Section: Transcranial Sonography In Parkinson's Diseasementioning
confidence: 99%
“…This procedure has been considered sensitive and reliable in detecting abnormalities of the basal ganglia of the brain, such as degeneration of the SN in idiopathic PD, lesion of the lentiform nucleus in idiopathic dystonia, and degeneration of the SN and the caudate nucleus in Huntington's disease, among others. The method is also useful in the differential diagnosis of movement disorders and to clarify some of their pathophysiological mechanisms (12)(13)(14)(15)(16) .…”
Section: Transcranial Sonography In Parkinson's Diseasementioning
confidence: 99%
“…Higher failure rates for transcranial sonography due to an insufficient bone window have been reported among Japanese, Taiwanese, South American, Australian, and South Korean populations. These differences may be caused by lower bone mineral density in these populations due to lower dietary calcium intake compared with Filipino and white populations 11 , 27 29 …”
Section: Discussionmentioning
confidence: 99%
“…These differences may be caused by lower bone mineral density in these populations due to lower dietary calcium intake compared with Filipino and white populations. 11,[27][28][29] Moreover, we examined whether repetitive measurements of the area of the substantia nigra increase diagnostic accuracy for PD. Indeed, we showed that repetitive measurements did increase the specificity and positive predictive value for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…We have read with special interest the article by Fernandes et al 1 entitled "Transcranial sonography as a diagnostic tool for Parkinson' s disease". These authors aimed to establish the percentage of subjects with adequated temporal bone windows for transcranial sonography (TCS) studies and also to revisit in a Brazilian sample the hypothesis that increased echogenic size of substantia nigra (SN) might distinguish Parkinson' s disease (PD) patients from healthy individuals.…”
Section: Dear Editorsmentioning
confidence: 99%